Grounded Theory Methodology: Comparison of Glaserian and Straussian Versions - Petružytė, Donata (Sociologija. Mintis ir veiksmas, 2008)
Grounded Theory is one of the most widely used methodologies in social sciences of modern days. Clear framing of differences of two principal versions of Grounded Theory (Glaserian and Straussian) is the essential question when one wants to understand it and make Grounded Theory research. Therefore in this paper it will be briefly presented Grounded Theory and analyzed differences of its two principal versions. At first it will be discussed the context of Grounded Theory origin and its contribution to the methodology of social sciences. It will be proceeded with coherent analysis of differences of both versions. In the beginning will be discussed historical aspects (the split between two co-originators which influenced further development of Grounded Theory methodology). Afterwards will be analyzed theoretical basis of Grounded Theory and discussed its place among quantitative and qualitative research methods. Focal attention in both topics will be given to the differences between Glaserian and Straussian versions. Ultimately it will be discussed various procedural and technical discrepancies. The analysis of differences leads to the conclusion that two versions of Grounded Theory can be treated as two substantially distinct methodologies.